The Value of honesty : the story of Confucius - Johnson, Spencer (La Jolla, CA : Value Comm., Inc. Pub, 1979)
A biography of the Chinese Philospher and teacher emphasizing his ideas about value of honesty.
Keywords: Confucius; Philosophers; Honesty